Why Effective Interventions Do Not Work for All Patients: Exploring Variation in Response to a Chronic Disease Management Intervention. Issue 8 (August 2018) - Edlind, Merritt; Mitra, Nandita; Grande, David; Barg, Frances K.; Carter, Tamala; Turr, Lindsey; Glanz, Karen; Long, Judith A.; Kangovi, Shreya
Abstract : Background: Half of all Americans have a chronic disease. Promoting healthy behaviors to decrease this burden is a national priority. A number of behavioral interventions have proven efficacy; yet even the most effective of these has high levels of nonresponse. Objectives: In this study, we explore variation in response to an evidence-based community health worker (CHW) intervention for chronic disease management. Research Design: We used a convergent parallel design that combined a randomized controlled trial with a qualitative process evaluation that triangulated chart abstraction, in-depth interviews and participant observation. Subjects: Eligible patients lived in a high-poverty region and were diagnosed with 2 or more of the following chronic diseases: diabetes, obesity, hypertension or tobacco dependence. There were 302 patients in the trial, 150 of whom were randomly assigned to the CHW intervention. Twenty patients and their CHWs were included in the qualitative evaluation. Results: We found minimal differences between responders and nonresponders by sociodemographic or clinical characteristics. A qualitative process evaluation revealed that health behavior change was challenging for all patients and most experienced failure (ie, gaining weight or relapsing with cigarettes) along the way. Responders seemed to increase their resolve after failed attempts at health behavior change, while nonresponders became discouraged and "shut down." Conclusions: Failure is a common and consequential aspect of health behavior change; a deeper understanding of failure should inform chronic disease interventions. Abstract : Supplemental Digital Content is available in the text.